Risk factors associated with severe systemic allergic reaction after wasp sting in subjects with a history of European hornet sting allergy - Perčič, Simona (Zdravstveno varstvo, 2024)
Aim: To make the treatment approach in patients suffering a European hornet sting allergy reaction more personalized, preparing them also for possible future risks. Methods: In Slovenia an extended retrospective observational cohort epidemiological study about the natural history of Hymenoptera venom sensitivity is in progress. The study is based on data from the healthcare records of the University Clinic Golnik (UCG) and data collected by a questionnaire sent to patients from May 2019 to April 2021. For a pilot study, we selected patients who were referred to UCG because of an allergic reaction to European hornet sting and had been re-stung later by a wasp (n=68). The association between severe systemic allergic reactions (SSAR) after wasp sting and potential risk factors in subjects with a history of hornet sting allergy was assessed univariately using the likelihood ratio test. Results: Among 68 European hornet allergic patients 27 reacted with an SSAR and 41 reacted with a mild SAR. Among 27 patients with SSAR, 4 reacted with an SSAR also to a subsequent wasp sting. Among 41 patients with a mild European hornet sting SAR nobody reacted with an SSAR to a subsequent wasp sting. The association between the severity of the wasp SAR reaction in European hornet allergic patients was statistically significant (p=0.022). Conclusion: Our results suggest that patients with severe European hornet SAR should be considered for wasp venom immunotherapy or prophylactic prescription of epinephrine auto-injector as they are at risk for an SSAR also after wasp string.
Keywords: alergija po piku kožekrilcev; European hornet sting; healthcare; hymenoptera allergy; javno zdravje; pik evropskega sršena; pik ose; public health; severe systemic allergic reactions; težka sistemska alergijska reakcija; wasp sting; zdravstvena oskrba